Comparison of Outcome of Perianal Block versus Saddle Block in the Treatment of Anal Fissure at a Tertiary Care Hospital - Muhammad Aqib Riaz; Ansari, Sajjad Ahmad; Sonia Khan; Raheel Anjum; Awan, Afzal Saeed; Kanwal, Saima (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the outcome of Perianal block versus Saddle block in the treatment of anal fissure using lateral sphincterotomy procedure.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital, Multan Pakistan, from Jun 2022 to Mar 2023.Methodology: The sample of 60 patients with anal fissures were randomly divided in two equal Groups (Group-A and B) by lottery method. Group-A patients underwent perianal block while Group-B patients received Saddle block. Both the Groups underwent lateral sphincterotomy procedure for the treatment of anal fissure. Pain assessment was done every hour for first 6 hours and then after 2 hours for the next 24 hours, and total pain-free period was defined as the mean time taken from administration of block till the time the patient required rescue analgesia (75 mg diclofenac sodium intramuscularly).Results: Males were (38)63.3%, whereas (22)36.7% were females. Mean age of these patients was 36.73±9.19 years (range; 22–58 years), and (43)71.7% were aged up to 40 years. Mean time taken for rescue analgesia in Group-A was 288.17±58.13 minutes versus 117.50±18.18 minutes in Group-B (p